Credit growth in Central and Eastern Europe: new (over)shooting stars? - Balázs Egert; Peter Backé; Tina Zumer (European Central Bank (ECB), 2006)
This paper analyzes the equilibrium level of private credit to GDP in 11 Central and Eastern European countries in order to see whether the high credit growth recently observed in some of these countries led to above equilibrium private credit-to-GDP levels. We use estimation results obtained for a panel of small open OECD economies (out-of-sample panel) to derive the equilibrium credit level for a panel of transition economies (in-sample panel). We opt for this (out-of-sample) approach because the coefficient estimates for transition economies are fairly unstable. We show that there is a large amount of uncertainty to determine the equilibrium level of private credit. Yet our results indicate that a number of countries are very close or even above the estimated equilibrium levels, whereas others are still well below the equilibrium level.
Keywords: C31; C33; E44; G21; 330; credit growth; credit to the private sector; equilibrium level of credit; initial undershooting; Transition Economies; Kreditgeschäft; Systemtransformation; Schätzung; Transformationsstaaten; Osteuropa